Are wicked problems really so wicked? Perceptions of policy problems. Issue 2 (10th June 2019) - Peters, B Guy; Tarpey, Matthew
Abstract: The concept of wicked problems has become widely used in policy analysis. The popularity of the concept has led to its overuse, and has produced significant conceptual stretching. This paper investigates the extent to which this stretching has led to the application of the concept to issues which are not 'wicked' in any meaningful sense. Based on a survey of policy experts, we find that few, if any, policy problems are perceived to have all the attributes of wicked problems. Although the concept does not appear useful in categorizing problems in a strict manner, the presence or absence of certain attributes can still be used in understanding the problems and in designing solutions for them.